Pengaruh firm size, corporate governance, dan karakteristik perusahaan terhadap manajemen laba - LAVENIA ARIFIN; NICKEN DESTRIANA (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this research is to analyze the effect of firm size, board of director, board of independence, audit quality, managerial ownership, institutional ownership, profitability, and leverage toward earnings management. This study tries to improve consistency of results from prior researchers. The sample of this study consist of 126 data from 42 non-financial sector companies that has been listing in Indonesia Stock Exchange for the period 2012 to 2014 by purposive sampling method. This study uses multiple regression method to investigate relation between each independent variable to earnings management. The research result shows that board of independence, institutional ownership, profitability, and leverage influence earnings management. On the other hand, firm size, board of director, audit quality, and managerial ownership do not influence earnings management.